Sugar provisioning maximizes the biocontrol service of parasitoids - Tena, Alejandro; Pekas, Apostolos; Cano, Dalmert; Wackers, Felix L.; Urbaneja, Alberto (2017)
There is increasing interest in the use of food supplements in agriculture to enhance the performance of parasitoids as part of conservation biological control. Nevertheless, there is limited evidence demonstrating the effectiveness of this approach, and this shortage of successful examples raises doubt regarding the validity of this approach. The use of sugar sources relies on tiered premises that: (i) parasitoids are sugar limited and (ii) this limitation is alleviated through the provision of sugar sources, thereby increasing both (iii) parasitoid fitness and (iv) the population density, which together lead to (v) an increase in parasitism. In the present study, we address these five premises through experiments examining the release of the parasitoid Aphytis melinus DeBach (Hymenoptera: Aphelinidae) into the citrus agroecosystem with and without sugars. The results demonstrated that A.melinus is sugar limited when honeydew producers are scarce in the field. The provision of sugars did not increase the sugar contents in A.melinus females but rather increased the realized fecundity in these parasitoids, suggesting that females use energy for foraging and oviposition. Sugar sources increased the parasitoid population density twofold, and this increase most likely reflects the enhanced parasitoid longevity. Higher population densities and the increased realized fecundity of A.melinus obtained from trees with sugars were reflected in a twofold increase of parasitized hosts. Synthesis and applications. This study provides the first evidence supporting the five premises underlying sugar provisioning for parasitoids and demonstrates the potential value of sugar provisioning to enhance natural pest control in agricultural systems. This study provides the first evidence supporting the five premises underlying sugar provisioning for parasitoids and demonstrates the potential value of sugar provisioning to enhance natural pest control in agricultural systems.